Mothers, Friends and Gender Identity - Claudia Olivetti; Eleonora Patacchini; Yves Zenou (Institute for the Study of Labor (IZA), 2013)
This paper explores a novel mechanism of gender identity formation. Specifically, we explore how the work behavior of a teenager's own mother, as well as that of her friends' mothers, affect her work decisions in adulthood. The first mechanism is commonly included in economic models. The second, which in social psychology is also emphasized as an important factor in gender identity formation, has so far been overlooked. Accordingly, our key theoretical innovation is how the utility function is modeled. It is assumed that an adult woman's work decisions are influenced by her own mother's choices as well as her friends' mothers' choices when she was a teenager, and the interaction between the two. The empirical salience of this behavioral model is tested using a network model specification together with the longitudinal structure of the AddHealth data set. We find that both intergenerational channels positively affect a woman's work hours in adulthood, but the cross effect is negative, indicating the existence of cultural substitutability. That is, the mother's role model effect is larger the more distant she is (in terms of working hours) from the friends' mothers.
Keywords: J22; Z13; 330; intergenerational transmission; gender identity; labor force participation; social networks; Stereotyp; Mütter; Weibliche Arbeitskräfte; Erwerbstätigkeit; Soziale Gruppe; Soziales Netzwerk; USA